Feasibility of Spirogyra majuscula and Cladophora fracta Algae on Growth with Different Concentrations of Sewage and Bioethanol Production - Raid K. Abed Alasady; Zaid S. Awad Alawady (Al-Qadisiyah Journal of Pure Science, 2018)
The current study targeted test the feasibility of two types of filamentous green algae [Spirogyra majuscula and Cladophora fracta on growth with different concentrations of sewage and the production of bio-ethanol, and to achieve that algae were isolated from the water of Al-Diwaniyah River/ city center and then reproduction in mass cultures for biomass in order to chemical analysis and bioethanol production.Algae were growth and development on (Chu-10) and optimum intensity of illumination for growth (1800 lux â€œPrevious workâ€) specific, by selecting the growth curve, a constant relative growth (K) and the rate of doubling time (G) for each alga, then algae were test growth on five concentrations of sewage, which is a collection of sewage with distilled water and the following percent: 10%, 20%, 40%, 80% and 100% (sewage water only), is then their production process of batch culture for the purpose of detecting dry their contents of total carbohydrates and susceptibility on the production of bio-ethanol from the fermentation of carbohydrates process and determine the concentrations at all sewage concentration to both algae respectively, the results showed that the rate of doubling time of algae, respectively, at the Chu-10 amounted to 0.97 and 1.08 compared to different concentrations of sewage, which did not give a significant effect of constant relative growth rate and rate of doubling time of algae under study while C. fracta gave higher relative to growth at all concentrations of sewage compared with S. majuscula except 40% concentration who recorded superior to last algae (0.297) compared with first algae (0.253), while the rate doubling time were higher in all concentrations in S. majuscula except concentration of 40% which was higher than the rate doubling time for the superior of C. fracta, which amounted to (1.014 and 1.190), respectively. Chemical analysis showed that of dry content of algae (S. majuscula and C. fracta) were grow on Chu-10 and the concentrations of sewage increase in their content of total carbohydrates, which increased with increasing concentrations of sewage down to the stock concentrate (100%) as the highest percentage of total carbohydrate were (26.19 and 30.29%), respectively, at 100% concentration with a superiority of C. fracta in the carbohydrate content of the S. majuscula at the same concentrations. Bioethanol output of fermentable carbohydrates to under study algae showed that the effect of different concentrations of sewage heterogeneous between algae in of productivity and the concentrations of the medium, reaching the highest content of S. majuscula is 33.44% when the concentration of 20%, while the 40% concentration giving higher content to C. fracta reached 35.33% compared to the same content when control treatment (Chu-10), which recoded (32.29 and 27.13)%, respectively, or compared with less content of bio-ethanol reached when 40% concentration where recorded (18.60 and 8.52)% to both algae respectively.